Model Pembelajaran Tahfizh Al-Qur’an Tematik (TQT) Kelas Online di Bait Al-Hikmah Foundation Malang - Reni Nur Farida; Faridi; Romelah (Universitas Darussalam Gontor, 2022)
This study aimed to describe the implementation of the Thematic Tahfizh learning online class and its evaluation at Bait al-Hikmah Foundation Malang. The type of this research is case study. It is located at Bait al-Hikmah Foundation, Jl. Tirtotaruno IX/28 Klandungan Landungsari Malang. The technique of the research consists of observation, interviews, and documentation with several informants, Such as education and religious administrators, teacher and TQT coordinators, and online class students. While, the data analysis utilized descriptive analysis. The results of this study can be concluded that: (1) The implementation of the Thematic Tahfidz al-Qur’an learning is based on many people who want to study religious knowledge and to learn the al-Qur’an in-depth, besides, they want to continue to exist in grounding the al-Qur’an, which can be reached by all communities, not only national but international community also. (2). Evaluation of the Thematic Tahfidz al-Qur’an learning includes 4 types, namely: evaluation of learning outcomes ( evaluation carried out after completing one theme), evaluation of grade promotion (evaluation carried out after completing several themes), evaluation of munaqasyah ( graduation stage after 3 months of learning).